2023
DOI: 10.1186/s40001-023-01043-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune-associated biomarkers identification for diagnosing carotid plaque progression with uremia through systematical bioinformatics and machine learning analysis

Abstract: Background Uremia is one of the most challenging problems in medicine and an increasing public health issue worldwide. Patients with uremia suffer from accelerated atherosclerosis, and atherosclerosis progression may trigger plaque instability and clinical events. As a result, cardiovascular and cerebrovascular complications are more likely to occur. This study aimed to identify diagnostic biomarkers in uremic patients with unstable carotid plaques (USCPs). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The WGCNA analysis was well‐described in our previous study 46 . In briefly, Figure 3A,B indicated that the best soft‐power value for IBD merged dataset (GSE75214 + GSE36807) was 16 according to scale independence and average connectivity.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The WGCNA analysis was well‐described in our previous study 46 . In briefly, Figure 3A,B indicated that the best soft‐power value for IBD merged dataset (GSE75214 + GSE36807) was 16 according to scale independence and average connectivity.…”
Section: Resultsmentioning
confidence: 52%
“…The WGCNA analysis was well‐described in our previous study. 46 In briefly, Figure 3A,B indicated that the best soft‐power value for IBD merged dataset (GSE75214 + GSE36807) was 16 according to scale independence and average connectivity. After modules merging, a total of 12 co‐expression modules were recognized, each corresponding to one colour (Figure 3D,E ).…”
Section: Resultsmentioning
confidence: 93%
“…Cheng et al identified eight pivotal genes by analyzing hub differentially expressed genes [ 19 ]. Chunjiang et al selected three hub genes for diagnosing carotid plaque progression [ 20 ]. Di et al used bioinformatics analysis to identify seven genes essential to late-stage carotid atherosclerosis markers [ 21 ].…”
Section: Methodsmentioning
confidence: 99%